Cervicitis - Estrada, Santiago (Medicina UPB, 1997)
A short and actualized revision on the subject of Cervicitis is done focusing especially on the etiopathogenic, clinical, and diagnostic aspeets through laboratory evaluation according to levels I,II, and III of attention and treatment.